Mobile financial services and financial inclusion: Is it a boon for savings mobilization? - Shem Alfred Ouma; Teresa Maureen Odongo; Maureen Were (Review of Development Finance, 2017)
The adoption of mobile telephony to provide financial services in Africa has become instrumental in integrating the hitherto unbanked segments of the population to the mainstream financial systems. This study sought to establish this linkage by examining whether the pervasive use of mobile telephony to provide financial services is a boon for savings mobilization in selected countries in sub Saharan Africa. The findings show that availability and usage of mobile phones to provide financial services promotes the likelihood of saving at the household level. Not only does access to mobile financial services boost the likelihood to save, but also has a significant impact on the amounts saved, perhaps due to the frequency and convenience with which such transactions can be undertaken using a mobile phone. Both forms of savings, that is, basic mobile phone savings stored in the phone and bank integrated mobile savings are likely to be promoted by use of mobile phones. Thus, growing and deepening the scope for mobile phone financial services is an avenue for promoting savings mobilization, especially among the poor and low income groups with constrained access to formal financial services.
Keywords: G20; G21; O30; E21; 650; Financial innovation; Mobile financial services; Savings